Optimization of Gluten-Free Tulumba Dessert Formulation Including Corn Flour: Response Surface Methodology Approach - Yildiz Önder; Bulut Birgül (Polish Journal of Food and Nutrition Sciences)
Tulumba dessert is widely preferred in Turkey; however, it cannot be consumed by celiac patients because it includes gluten. The diversity of gluten-free products should be expanded so that celiac patients may meet their daily needs regularly. In this study, corn flour (CF) / potato starch (PS) blend to be used in the gluten-free tulumba dessert formulation was optimized using the Response Surface Methodology (RSM). Increasing ratio of PS in the CF-PS led to a decrease in hardness of the dessert and to an increase in expansion, viscosity, adhesiveness, yield of dessert both with and without syrup (P<0.05). When considering the properties used in optimization process, the optimum formulation was found to be as 201.52 g water and 0.18 g CMC and 100 g blend of CF-PS at the rates of 59:41. In sensory evaluation test, appearance, symmetry, crispness and aftertaste properties of the gluten-free dessert prepared from this formulation were very close to control sample (P>0.05), additionally these desserts had a much higher sensory score compared to the control sample in terms of the overall quality and pore structure (P<0.05).